СУЩНОСТЬ И ЭВОЛЮЦИЯ ФОРМИРОВАНИЯ «КОНФЕССИОНАЛЬНОЙ ДЕМОКРАТИИ»: СРАВНИТЕЛЬНЫЙ АНАЛИЗ СТРАН БЛИЖНЕГО ВОСТОКА И ЦЕНТРАЛЬНОЙ АЗИИ - Нуров, Мархаббат; Алияров, Есенжол; Несипкалиев, Даурен (Аль-Фараби, 2024)
The article pays special attention to the process that determines the essence and evolution of the formation of confessional democracy, its development. This is due to the fact that confessional democracy, characterized by the intersection of religious identity and political governance, is a difficult phenomenon for a multi-confessional country. At the same time, on the basis of a multidimensional analysis of political, social and institutional factors, a comparative analysis of confessional democracy in the Middle East and Central Asia is carried out, its historical roots, differences, dynamics in modern conditions and directions of long-term development are considered. Of course, there is also the role of religion in politics, the impact of globalization and a number of key trends that contribute to political pluralism and political stability. Analyzing the situation in world geopolitics today, the essence, evolution and consequences of the political model are investigated. In a historical context, based on institutional dynamics and events taking place in different parts of the modern world, the study reflects common features, differences and interregional trends in the formation of confessional democracy. Based on the analysis of specific examples in the Middle East and Central Asia, the article reveals the problems and possibilities of governing various societies in the context of religious pluralism. In this regard, some important issues of the role of confessional democracy in the realities of Kazakhstan will be analyzed. Keywords: confessional democracy, Islam, Middle East, Central Asia, religious identity, secularism, political governance.